Music, longing and belonging : articulations of the self and the other in the musical realm - Waligórska, Magdalena (Cambridge Scholars Publishing, 2013)
With contributions from musicologists, historians, sociologists, anthropologists and literary scholars, this book provides an interdisciplinary perspective on how different modes of musical sociability - ranging from opera performances to collective singing and internet fan communities - inspire ""imagined communities"" that not only transcend national borders, but also challenge the boundaries between the self and the other. While the relationship between music and nationhood has been widely r ...